Multisensorielle Navigation und Kartierung in schwierigen Bedingungen - Doer, Christopher (KIT Scientific Publishing, 2023)
Robust navigation as well as mapping of the environment are critical for autonomous aerial vehicles. This is especially challenging in poor visual conditions or degraded GNSS. Therefore, this thesis proposes multi-sensor fusion approaches based on FMCW radar, cameras and inertial sensors. These approaches can cope with such challenging conditions as demonstrated in different scenarios.